Sonographically Guided Percutaneous Sectioning of the Coracohumeral Ligament for the Treatment of Refractory Adhesive Capsulitis: Proof of Concept. Issue 12 (31st August 2020) - Wahezi, Sayed; Yerra, Sandeep; Rivelis, Yulia; Sitapara, Kishan; Gonzalez, David; Downie, Sherry; Jain, Ruchi; Deer, Tim; Abd-Elsayed, Alaa; Gulati, Amit
Abstract: Introduction: Treatment options are limited for nonsurgical chronic refractory cases of adhesive capsulitis. We describe a novel percutaneous tenotomy technique for coracohumeral ligament interruption with cadaveric validation. Objective: The objective of this study was to describe and validate a novel technique for percutaneous interruption of the coracohumeral ligament. Design: Cadaveric study. Setting: Academic tertiary care center. Methods: Eight cadavers underwent ultrasound (US)-guided percutaneous incision of the coracohumeral (CHL) ligament. Performance of the procedure requires that the practitioner make oscillatory motions with a needle that uses ultrasound energy to cut through tissue. Each pass removes a pinhead-sized amount of tissue. The number of passes and the cutting time are recorded during the procedure. As a standard for this procedure does not exist, the authors created their own based on the preclinical information presented here. Postprocedure dissection was performed to assess the extent of CHL interruption and injury to surrounding tissue. Results: The average resection time was seven minutes, requiring 500 passes. The technique described in this paper completely interrupted the CHL in all subjects. Cadaveric analysis demonstrated interruption of the CHL with respect to control shoulders requiring an average of seven minutes of cutting time and ∼500 micro-perforations. Conclusion: US-guided percutaneous CHL ligament sectioning is possible with a commercially available ultrasonic probe.